2002
DOI: 10.1093/oxfordjournals.rpd.a006783
|View full text |Cite
|
Sign up to set email alerts
|

Observation of Radiation-specific Damage in Human Cells Exposed to Depleted Uranium: Dicentric Frequency and Neoplastic Transformation as Endpoints

Abstract: Depleted uranium (DU) is a dense heavy metal used primarily in military applications. Published data from our laboratory have demonstrated that DU exposure in vitro to immortalised human osteoblast cells (HOS) is both neoplastically transforming and genotoxic. DU possesses both a radiological (alpha-particle) and chemical (metal) component. Since DU has a low specific activity in comparison to natural uranium, it is not considered to be a significant radiological hazard. The potential contribution of radiation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(35 citation statements)
references
References 0 publications
3
31
0
1
Order By: Relevance
“…While these findings might suggest these heavy metals are unknown. Our laboratory has used that the chemical component of DU could be primarily both an in vitro human cell-model and rodent studies to responsible for the transforming effects, recent cellular examine the potential late health effects of these heavy transformation and cytogenetic findings from our laboratory have shown that alpha particles are involved in the neoplastic transformation process [13]. Furthermore, the *Corresponding author.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…While these findings might suggest these heavy metals are unknown. Our laboratory has used that the chemical component of DU could be primarily both an in vitro human cell-model and rodent studies to responsible for the transforming effects, recent cellular examine the potential late health effects of these heavy transformation and cytogenetic findings from our laboratory have shown that alpha particles are involved in the neoplastic transformation process [13]. Furthermore, the *Corresponding author.…”
Section: Introductionmentioning
confidence: 99%
“…Bystander effects, whereby cells that are not directly Genomic instability ↑ Genotoxicity / genomic instability [11][12][13] exposed to radiation exhibit adverse biological effects, however assumes that the second-order rate constant for have been observed in a number of experimental systems.…”
Section: Introduction Metals Data From Our Laboratory Have Demonstmentioning
confidence: 99%
See 1 more Smart Citation
“…Miller et al (1998), using in vitro tests with DU chloride, found that human osteoblast cells can be transformed into the tumorigenic phenotype. The authors of the study point out that the dose-effect relationship is similar to that observed for nonradioactive heavy metals; however, a later study (Miller et al, 2002) showed an approximately linear relationship between transformation frequency and specific activity (nuclear disintegrations/s Á g) for the same uranium concentrations. Also, Miller observed a significant increase in dicentric frequency for in vitro tests with DU that was not observed for nonradioactive heavy metals.…”
Section: Chemical and Synergistic Effects On Cancermentioning
confidence: 57%
“…Reports in the popular press of serious health effects from DU exposure often include misinterpretations of scientific reports, unsubstantiated claims, and false claims. Some excellent scientific studies have investigated DU health effects at the cellular level (e.g., Miller et al, 2002) or by testing animals exposed to DU (e.g., Domingo et al, 1989). These studies suggest possible chemically induced cancer risks, birth defects, immune system impairment, etc.…”
Section: Introductionmentioning
confidence: 99%